Multiple Choice Question (MCQ)

Simplify \dfrac{a^2-b^2}{ab}-\dfrac{ab-b^2}{ab-a^2} , its result is

  1. ×

    \dfrac{a^2-b^2+b}{a}

  2. \dfrac{a}{b}

  3. ×

    -\dfrac{a}{b}

  4. ×

    \dfrac{a^2+2b^2}{ab}

Collected in the board: Fractions

Steven Zheng posted 1 year ago


Answer


  1. \dfrac{a^2-b^2}{ab}-\dfrac{ab-b^2}{ab-a^2}

    = \dfrac{a^2-b^2}{ab} - \dfrac{b(a-b)}{a(b-a)}

    = \dfrac{a^2-b^2}{ab} +\dfrac{b}{a}

    = \dfrac{a^2-b^2}{ab} +\dfrac{b^2}{ab}

    =\dfrac{a^2}{ab}

    =\dfrac{a}{b}

Steven Zheng posted 1 month ago

Scroll to Top